2011
DOI: 10.1080/10926771.2011.629342
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Association between Difficulties with Emotion Regulation and Dating Violence Perpetration

Abstract: The perpetration of aggression in dating relationships is a prevalent problem among college students. Research that examines factors related to perpetrating dating violence is needed, as this could help guide prevention programming. This study examined how emotion regulation is related to dating violence perpetration among male and female college students (N = 440). Findings showed that the association between broad difficulties with emotion regulation, as well as more specific emotion regulation problems, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
132
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(152 citation statements)
references
References 38 publications
17
132
0
1
Order By: Relevance
“…Several studies have linked the dysregulation of emotion to impulsive-type aggression (Davidson, Putnam, & Larson, 2000;Strüber, Lück, & Roth, 2008), similar to that occurring in IPA, as well as IPA perpetration specifically (McNulty & Hellmuth, 2008). Findings that IPA perpetrators experience difficulties with emotion regulation (Gratz, Paulson, Jakupcak, & Tull, 2009;Shorey, Brasfield, Febres, & Stuart, 2011a;Stuart et al, 2006) suggest that regulation of negative affect in response to instigating triggers may be an important factor contributing to IPA. For example, problems controlling emotional impulses and believing one has limited approaches to managing negative affect are related to increased IPA perpetration by men (Gratz & Roemer, 2004;Shorey et al, 2011a;Tager, Good, & Brammer, 2010).…”
Section: Emotion Regulation and Ipamentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have linked the dysregulation of emotion to impulsive-type aggression (Davidson, Putnam, & Larson, 2000;Strüber, Lück, & Roth, 2008), similar to that occurring in IPA, as well as IPA perpetration specifically (McNulty & Hellmuth, 2008). Findings that IPA perpetrators experience difficulties with emotion regulation (Gratz, Paulson, Jakupcak, & Tull, 2009;Shorey, Brasfield, Febres, & Stuart, 2011a;Stuart et al, 2006) suggest that regulation of negative affect in response to instigating triggers may be an important factor contributing to IPA. For example, problems controlling emotional impulses and believing one has limited approaches to managing negative affect are related to increased IPA perpetration by men (Gratz & Roemer, 2004;Shorey et al, 2011a;Tager, Good, & Brammer, 2010).…”
Section: Emotion Regulation and Ipamentioning
confidence: 99%
“…Findings that IPA perpetrators experience difficulties with emotion regulation (Gratz, Paulson, Jakupcak, & Tull, 2009;Shorey, Brasfield, Febres, & Stuart, 2011a;Stuart et al, 2006) suggest that regulation of negative affect in response to instigating triggers may be an important factor contributing to IPA. For example, problems controlling emotional impulses and believing one has limited approaches to managing negative affect are related to increased IPA perpetration by men (Gratz & Roemer, 2004;Shorey et al, 2011a;Tager, Good, & Brammer, 2010). Similarly, in a sample of newlywed couples, Mc-Nulty and Hellmuth (2008) found that husbands' variability in past-week negative affect was related to increased IPA perpetration by the husband.…”
Section: Emotion Regulation and Ipamentioning
confidence: 99%
See 1 more Smart Citation
“…First, early aversive histories/childhood maltreatment has been shown to be a direct predictor of deficits in emotion regulation [25][26][27] as suggested by the AAM. Second, consistent with the AAM hypothesis that deficits in emotion regulation would be central to understanding the relationship between anger and violent behaviour, studies have confirmed the important role of deficits in emotion regulation in the understanding and prediction of violent behaviour [18,19,[28][29][30][31][32]. Finally, and of significance, a recent study confirmed that while childhood maltreatment, early maladaptive schemas, deficits in emotion regulation, and the experience of anger together contribute to the manifestation of violence within relationships, consistent with the AAM, deficits in emotion regulation was found to be the essential pathway by which childhood maltreatment results in the manifestation of violence [19].…”
Section: Introductionmentioning
confidence: 67%
“…The dysregulation of emotion is associated with impulsive aggression (Davidson, Putnam, & Larson, 2000;Strüber, Lück & Roth, 2008) and the dysregulation of negative emotion specifically has been linked to IPA perpetration (McNulty & Hellmuth, 2008). In addition, research demonstrates that greater difficulties with emotion regulation are related to greater IPA perpetration among both men and women (Berzenski & Yates, 2010;Gratz et al, 2009;Shorey, Brasfield, Febres, & Stuart, 2011;Shorey, Cornelius, & Idema, 2011;Watkins, Maldonado, & DiLillo, in press). Specifically, individuals who have greater difficulties controlling impulses when upset and report more limited strategies in managing negative emotions also report perpetrating greater IPA perpetration (Gratz & Roemer, 2004;Shorey, Cornelius et al, 2011;Watkins et al, in press).…”
Section: Emotion Emotion Regulatory Strategies and Ipamentioning
confidence: 99%